Cross Sectional Study on the Relationship Between Personal, Social, Family Factors and Depression Among the Elderly Residents of Zone X, San Andres, Manila - 4 0 16; 5
The purpose of this study was to determine the prevalence of depression and the factors that contribute to development of depression among the elderly. This study is a cross-sectional inferential study using an interview schedule that measured the depression status of the elderly with the Geriatric Depression Scale; current physical health status with the Instrumental Activities of Daily Living Scale; social support with the Lubben Social Network Scale; family function with the APGAR Scale; and religious participation and community function with the items developed by the researchers. The study was conducted in Zone X of San Andres, Manila. The sample consisted of 189 elderly, who consented to be part of the study, with range from 60 to 87 yaers old. The study utilized Chi Square Test of Association and the Odds Ratio between the above said tests and depression. A total of 59 out of 189 were measured to be depressed indicating a 31.2% prevalence of depression among the elderly. The dependent elderly were found to be 3 times more likely to be prone to depression than the independent elderly (p=.0035). While the isolated elderly were found to be 4 times more likely to be prone to depression than the elderly with low risk for isolation (p=.006). The elderly, who belong a severely dysfunctional family were found to be 14 times more likely to be prone to depression than those belonging to a highly functional family (p=.0001) On the other hand, the elderly, who were measured with poor community role were found to be 5 times more likely to be prone to depression (p=.0074). While the elderly with poor religious participation (p=.0264). The results of this study suggest that poor physical health status, social support, community role, and family function of an elderly contribute to the development of depression among the elderly.
Keywords: 2 -- 0; 6; 20; 20; 2